Inquiring together: A pre-participation phase for a coteaching clinical practice model in teacher education. (September 2022) - Rees, Carol; Murphy, Colette; Kaur, Rupinder Deol; Brown, Alexis
Abstract: This qualitative case study focused on the pre-participation phase of a three-year trial-run of a coteaching model for clinical practice within a teacher education program in western Canada. In this two-day workshop, teacher candidates, teacher mentors and faculty mentors worked in inter-professional groups on novel activities to discuss potential advantages and challenges. They identified five key issues necessary for the success of coteaching in their local context: Time, Building Relationships, Communication, Students See Teachers as Equal Partners, Engagement and Active Contribution. This pre-participation phase provided crucial support for upcoming coteaching by allowing concerns to be voiced and breaking down hierarchies. Highlights: Exploring ideas for a coteaching model for clinical practice in a local context. The importance of the pre-participation phase for preparing for coteaching. Novel activities for sharing multiple perspectives across professional groups.